Channel encroachment and logistics integration strategies in an e-commerce platform service supply chain - He, Peng; He, Yong; Tang, Xiaoying; Ma, Shigui; Xu, Henry (International journal of production economics, 2022)
This paper considers an e-commerce platform service supply chain (PSSC) consisting of a manufacturer, an e-commerce platform, and a possible third-party logistics service company (3 PL) and aims to explore the impacts of the manufacturer's channel encroachment and the e-commerce platform's logistics integration. Our research pinpoints that no matter whether the manufacturer implements an online channel encroachment or not, the platform's complete logistics integration strategy benefits the whole supply chain and its members. Counter-intuitively, we propose a partial logistics integration strategy, which outperforms the complete logistics integration strategy for the manufacturer and the entire PSSC. However, it underperforms the complete logistics integration strategy for the platform, even worse than the logistics outsourcing strategy in some situations. We further design two coordination mechanisms to achieve a three-win situation. Lastly, we find that the platform's complete (or partial) logistics integration strategy can effectively deter the manufacturer's channel encroachment under certain conditions. Besides, the manufacturer's offline channel encroachment would hurt himself when the logistics service efficiency is relatively high. Under an information asymmetry setting, it shows that a larger gap between two logistics cost states would discourage the manufacturer from implementing a channel encroachment strategy.